Phase Two Steroid Metabolism and Its Roles in Breast and Prostate Cancer Patients - McNamara, Keely M.; Nakamura, Yasuhiro; Miki, Yasuhiro; Sasano, Hironobu (Frontiers in Endocrinology, 2013)
Breast and prostate cancer are diseases in which steroids and steroid metabolism could markedly influence clinical outcomes for patients. In both malignancies the modification of ketone and hydroxyl groups attached to the steroid backbone (phase one metabolism) has been examined in detail but the conjugation reactions (phase two metabolism) have not been extensively studied. Therefore, in this review we aim to summarise phase two metabolism in breast and prostate cancers from a number of perspectives, including the impact of variation in serum levels of conjugated steroids, tissue and pathology specific expression of phase two enzymes, and consequences of genetic variations of these conjugation enzymes. In addition to this biological perspective, we will also address current pharmacological efforts to manipulate phase two metabolism as a potential therapy for hormone dependent cancers, including clinical trials of STS inhibitors and preclinical STS inhibitor development. While this review is not intended to cover any one particular area in great technical depth, it is intended as an introduction to and/or update on the importance of variance in phase two metabolic pathways in breast and prostate cancers.